Central Plasticity of Cutaneous Afferents Is Associated with Nociceptive Hyperreflexia after Spinal Cord Injury in Rats - Hyun Joon Lee; Patrick S. Malone; Jumi Chung; Jason M. White; Natalee Wilson; Jason Tidwell; Keith E. Tansey (Neural Plasticity)
Electrical stimulations of dorsal cutaneous nerves (DCNs) at each lumbothoracic spinal level produce the bilateral cutaneus trunci muscle (CTM) reflex responses which consist of two temporal components: an early and late responses purportedly mediated by Aδ and C fibers, respectively. We have previously reported central projections of DCN A and C fibers and demonstrated that different projection patterns of those afferent types contributed to the somatotopic organization of CTM reflex responses. Unilateral hemisection spinal cord injury (SCI) was made at T10 spinal segments to investigate the plasticity of early and late CTM responses 6 weeks after injury. Both early and late responses were drastically increased in response to both ipsi- and contralateral DCN stimulations both above (T6 and T8) and below (T12 and L1) the levels of injury demonstrating that nociceptive hyperreflexia developed at 6 weeks following hemisection SCI. We also found that DCN A and C fibers centrally sprouted, expanded their projection areas, and increased synaptic terminations in both T7 and T13, which correlated with the size of hemisection injury. These data demonstrate that central sprouting of cutaneous afferents away from the site of injury is closely associated with enhanced responses of intraspinal signal processing potentially contributing to nociceptive hyperreflexia following SCI.